Edible Coating Combining Liquid Smoke from Oil Palm Empty Fruit Bunches and Turmeric Extract to Prolong the Shelf Life of Mackerel - Muhammad Faisal; Asri Gani; Murna Muzaifa; M. Bagas Heriansyah; Hera Desvita; Suraiya Kamaruzzaman; Ahmad Sauqi; Daru Ardiansa (Foods)
This research aimed to evaluate the use of edible coating from a combination of liquid smoke and turmeric extract as a preservative for mackerel at room temperature. Liquid smoke was obtained from the pyrolysis of oil palm empty fruit bunches (OPEFB) at a temperature of 380 °C and purified by distillation at 190 °C. Liquid smoke with a concentration of 3% was combined with turmeric extract at a ratio of 2, 4, 6, and 8 g/L (CLS 2:1, CLS 4:1, CLS 6:1 and CLS 8:1). TVB-N testing showed that the mixture of liquid smoke and turmeric at a ratio of CLS 6: 1 and CLS 8: 1 maintains the freshness of fish for 48 h. Meanwhile, organoleptic testing reports that the best mixture was CLS 8:1. The number of colonies in the CLS 2:1, CLS 4:1, CLS 6:1, and CLS 8:1 mixtures were 4.92, 4.92, 4.16, and 4 × 10⁵ colonies/g after 44 h of soaking. The MPN test result at 48 h of soaking is 1.1 × 103 MPN/g. Generally, mackerel preserved with a mixture of turmeric extract and liquid smoke with a ratio of 8:1 can be consumed up to a shelf life of 48 h at room temperature storage.